Pengaruh Promosi, Pengetahuan Produk, dan Kepercayaan terhadap Minat Pembelian Polis Asuransi Syariah pada Masyarakat Muslim Kota Bandung - Dhimas Bramantyo Panji Pangarso; Vita Sarasi (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
Despite the country’s muslim-majority population, the penetration of Islamic insurance in Indonesia remains relatively low. One of the main challenges lies in the limited financial literacy and lack of public trust toward Islamic insurance products. As part of West Java Province, the city of Bandung has one of the largest Muslim populations in Indonesia, characterized by a high level of awareness toward halal products. This study aims to analyze the influence of promotion, product knowledge, and trust on the purchase intention of Islamic insurance policies among the muslim community in Bandung. A quantitative approach was employed using a survey method involving 141 respondents, with data analyzed through Structural Equation Modeling (SEM) using SmartPLS 3.2.9. The results indicate that promotion, product knowledge, and trust each have a positive and significant effect on the intention to purchase Islamic insurance policies. These findings highlight the importance of informative promotional strategies, improved literacy in Islamic insurance, and the need to strengthen public trust toward Islamic financial institutions. This research is expected to serve as a reference for Islamic insurance providers in developing effective and sustainable marketing strategies.